Variação nas condições de balneabilidade das praias urbanas de Maceió ao longo de uma década - Melo, Milena Bandeira de (2016)
Recreational water quality relies on objective water quality criteria. These criteria are based on fecal indicator bacteria monitoring and their concentrations confronted with pre-established standards. Recreational water quality of Alagoas coastal beaches is monitored by the State of Alagoas Environmental Institute (IMA/AL). This study aimed to evaluate the recreational water quality of the main urban beaches of Maceio city over a decade, through the collection and analysis of official data of IMA/AL from 2006 to 2015. In the last three years there has been general worsening on the quality of Pajuçara and Ponta Verde Beaches. Analyses were performed in storm drains that flow into the surroundings of recreational water quality monitoring stations included in this study. Some samples presented fecal indicator concentrations (enterococci) near the concentration found in sewage samples. Information was gathered regarding the sewage collection and transport system in the studied region. It was found that the decline in recreational water quality is directly related to systematic sewer overflows that have been occurring in the collection system, and this sewage has been reaching the beaches through the storm drainage system. The situation exposed in this research emphasizes the importance of publicizing the recreational water quality conditions of the touristic beaches of Maceio city by the competent authorities.